The relationship between physical activity and depression among community-dwelling adults in Wuhan, China - Wu, Kai-Ge; Chen, Si-Jing; Hu, Ya-Ni; Mei, Shu-Fang; Chen, Wen-Cai; Huang, Xian-E; Xu, Zai-Feng; Li, Ming-Chao; Zhong, Bao-Liang; Liu, Xiu-Jun (Frontiers in Psychiatry, 2023)
Background While the association between physical activity (PA) and depression has been established, there is limited research on the effect of PA on the risk of depression among Chinese individuals. Thus, this study aimed to investigate the relationship between PA and depression among Chinese individuals. Methods We used a stratified random sampling approach to recruit participants from five urban districts in Wuhan, China. A total of 5,583 permanent residents aged 18 years or older completed questionnaires, which included the International Physical Activity Questionnaire Short Form (IPAQ-SF) to measure PA, and the 9-item Patient Health Questionnaire (PHQ-9) to evaluate depressive symptoms. To control for potential confounders, multiple logistic regression was employed to assess the association of PA with depression. Results The depression group had significantly lower weekly PA levels, measured in metabolic equivalent of task-minutes per week (MET-min/w), compared to the non-depression group [1,770 (693–4,200) MET-min/w vs. 2,772 (1,324–4,893) MET-min/w, p < 0.001]. In the fully adjusted model, the moderate and high PA level groups had lower odds ratios (ORs) for depressive symptoms compared to the low PA level group [OR (95% confidence interval (CI)) = 0.670 (0.523–0.858), 0.618 (0.484–0.790), respectively]. Among males, moderate and high levels of PA were associated with lower risk of depression compared to low PA levels [OR (95% CI) = 0.417 (0.268–0.649), 0.381 (0.244–0.593), respectively]. However, this association was not observed in females [OR (95% CI) = 0.827 (0.610–1.121), 0.782 (0.579–1.056), respectively]. The study found a significant interaction between PA levels and gender in relation to depression (P for interaction = 0.019). Conclusion The findings suggest a negative association between PA and risk of depressive symptoms, indicating that moderate to high levels of PA may serve as a protective factor against depressive symptoms.